b n advanced resource book /c - Hewings, Ann.; Hewings, Martin (b, 2005)
Routledge Applied Linguistics is a series of comprehensive resource books, providing students and researchers with the support they need for advanced study in the core areas of English Language and Applied Linguistics.Each book in the series guides readers through three main sections, enabling them to explore and develop major themes within the discipline: Section A, Introduction, establishes the key terms and concepts and extends readers' techniques of analysis through practical application, Section B, Extension, brings together influential articles, sets them in context, and discusses their contribution to the field, Section C, Exploration, builds on knowledge gained in the first two sections, setting thoughtful tasks around further illustrative material. This enables readers to engage more actively with the subject matter and encourages them to develop their own research responses, Throughout the book, topics are revisited, extended, interwoven and deconstructed, with the readers' understanding strengthened by tasks and follow-up questions.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general; Context (Linguistics)